Health seeking behaviour among post-menopausal women: a knowledge, attitude and practices study - Khan, Samreen; Shukla, Mahesh K.; Priya, Neha; Ansari, M. Athar (International Journal Of Community Medicine And Public Health, 2016)
Background: Ageing women suffer problems associated with senility along with that of the reproductive tract changes. Unless the woman is treated as a whole, her problem is actually not addressed. With this background, the present study was undertaken with the following objectives: to identify the major health problems of postmenopausal women, to determine the level of knowledge, attitude and practices of postmenopausal women in terms of seeking Health care facilities for their problems and to determine the utilization pattern and barriers to utilization of health care services by these women. Methods: It was a community based cross-sectional study conducted in the registered field practice areas of the Department of Community Medicine, Jawahar Lal Nehru Medical College and Hospital, Aligarh from June, 2012 to May, 2013. The study tools consisted of pre-tested and semi-structured proforma and standard Menopausal Rating scale (MRS) questionnaire. Results: Psychological symptoms were reported by 34.3%, somatological symptoms by 60.1% and urogenital symptoms by 59.6% of the study population. To deal with these problems, majority in urban areas said that a doctor should be consulted whereas majority in rural areas either said that they did not know what could be done or traditional or home-based measures should be resorted to. Conclusions: A large majority suffered from ill-health. Most rural women had no access to health services. Lack of knowledge and traditional practices were barriers to utilization of services.